Single-cell RNA Sequencing Analysis Reveals the Regulatory Functions of Copines Family Genes in Testicular Cancer Progression - Li, Nan; Yu, Kai; Huang, Delun; Zhu, Xuehong; Lin, Zhong (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2026)
AimsThe aim of this study is to investigate the expression patterns and regulatory functions of Copines family genes in different cellular subpopulations in testicular cancer based on single-cell data and to analyze the regulatory mechanism of Copines family genes in cancer.BackgroundTesticular cancer is a frequently diagnosed male tumor. Emerging evidence suggests that Copines family genes are implicated in a variety of cancer phenotypes and cancer progression. Analyzing the expression pattern of Copines family genes in testicular cancer may help improve the treatment efficacy of the cancer.ObjectiveThis study sought to characterize the expression profiles of Copines family genes in the cellular subpopulations of testicular cancer and to identify key signaling pathways through which they regulate cancer progression.MethodsBased on single-cell transcriptomic data of testicular cancer, we classified testicular cancer cell subpopulations and analyzed the expressions of Copines family genes in each subpopulation. Cell subpopulations were grouped according to the expression levels of Copines family genes, and differentially expressed Copines family genes between the groups were screened by differential expression analysis. Functional enrichment analysis on the differentially expressed genes (DEGs) was performed with a clusterprofiler package. Functional pathways enriched by the Copines family genes were calculated by AUCell enrichment score. Copy number variation (CNV) analysis was performed using inferCNV to analyze gene mutation patterns across cellular subpopulations, and pseudotime analysis was conducted using Monocle to infer cellular differentiation pathways of cellular subpopulations.ResultsSingle-cell clustering identified four major cell subpopulations, namely, NK/T cells, tumor cells, B cells, and macrophages. Notably, the control samples had a relatively small proportion of tumor cells. Further clustering of the tumor cells identified six cell subpopulations, among which multiple Copines genes, especially CPNE1 and CPNE3, showed a high expression. The testicular cancer samples were grouped by the expression patterns of Copines genes, and the DEGs between groups included GNLY, MGP1, CFD2, CCL21, SPARCL13 as well as some other genes involved in the malignant progression of cancer. Pseudotime analysis showed that the upregulated genes were enriched in cell migration and PI3K-Akt pathway, while the downregulated genes were related to immunity. This indicated that the Copines genes regulated the cellular heterogeneity and malignant transformation in testicular cancer.ConclusionThis study revealed the potential molecular mechanism through which Copines family genes drove the progression of testicular cancer through regulating PI3K-Akt signaling pathway and cell cycle, providing a new target for the development of precision treatment targeting Copines family genes and prognostic assessment of the cancer.
Keywords: Copines